Evaluation of microstructural and microchemical aspects of high density concrete exposed to sustained elevated temperature. (15th November 2016) - Sivathanu Pillai, C.; Santhakumar, A.R.; Poonguzhali, A.; Pujar, M.G.; Ashok Kumar, J.; Preetha, R.; Kamachi Mudali, U.
Abstract: High density concrete is widely used as a primary material for radiation shielding due to numerous advantageous properties such as, strength, durability and ease of fabrication in comparison with other construction materials. As concrete is subjected even to high temperature environment in a nuclear reactor, the selection of concrete aggregates depends upon the exact application of the concrete. ACI limits the normal operating temperature in concrete structures to 65 °C in general and 90 °C locally, as exposure of concrete to high temperature induces complex changes in the moisture content as well as chemical composition of the cement paste and mismatch in thermal expansion leads to internal stresses and microcracking in the concrete constituents (aggregate and cement paste). Present research work is to investigate the suitability of concrete ingredients for producing high-performance high density concrete, of different densities using different types of aggregates (heamatite and steel shots) and studying the physicochemical changes in them due to a constant exposure at 120 °C as in a sodium cooled reactor. The results indicated heavy moisture loss in the first seven days of exposure and reduction in the mechanical properties, followed by increase in strength on continued exposure. Microstructure and morphological variations in thermally aged fractured specimens were used to explain the above variation in the mechanical properties.